Aplikasi Pupuk Cair dari Limbah Organik dan Nano Nutrien pada Berbagai Varietas Ubi Kayu (Manihot esculenta Crantz) - Iftitah, Siti N; Susilowati, Yulia E; Historiawati, Historiawati; Astiningrum, Murti; Novita, Woro A; Damayanti, Alfina R (JURNAL BUDIDAYA PERTANIAN, 2023)
Increasing cassava production can be achieved among others by giving various forms of fertilizer to provide the nutrients needed by plants. This research aimed to determine the effect of applying liquid fertilizer from organic waste and nano nutrients on the growth of various cassava varieties. The research was carried out from March to November 2023, at the experimental field of the Faculty of Agriculture, Tidar University, in Sidorejo Village, Bandongan District, Magelang Regency. The experimental research was carried out using a factorial design in a Split Plot experiment with 3 replications as blocks. The first factor was the types of varieties consisting of Sticky Rice, Butter, Klenteng, and Rengganis. The second factor as a subplot is liquid fertilizer in the form of slaughterhouse waste and nano nutrients. The data were analyzed using analysis of variance and followed by a Least Significant Difference test at the a = 0.01 and 0.05 levels, as well as the orthogonal test. The results showed that the type of variety used did not have a significant effect on the variables of plant height increase, branch number, branch height, leaf number, root number, root fresh weight, and photosynthesis rate. Rengganis variety had a very significant effect on leaf chlorophyll levels. The application of liquid organic fertilizer, both from slaughterhouse waste and nano nutrients, did not have a significant effect on the variables of plant height increase, branch number, branch height, leaf number and root fresh weight. Liquid fertilizer from slaughterhouse waste hah a significant effect on root number, whereas nano nutrient fertilizer had a significant effect on the rate of photosynthesis and has a very significant effect on leaf chlorophyll content. There was an interaction between varieties and the provision of liquid fertilizer on leaf chlorophyll content.